EVALUASI SISTEM KEARSIPAN PENDIDIKAN DI INDONESIA PERSPEKTIF MANAJEMEN DAN TRANSFORMASI DIGITAL - Hanan Nur Ramadhani; Siti Reskia Rofiah; Yafi Muhammad Abdilah; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The educational archival system plays a crucial role in supporting effective, transparent, and accountable governance within educational institutions. However, archival practices in Indonesia still face several challenges, including unsystematic archive management, low digital literacy among educational staff, and limited technological infrastructure. This study aims to evaluate the educational archival system in Indonesia from the perspectives of management and digital transformation. The research employs a qualitative approach using literature review and descriptive analysis. The findings indicate that archival systems in education are still largely conventional and not yet digitally integrated. Furthermore, the implementation of digital transformation is hindered by the lack of comprehensive policies, insufficient human resource competencies, and inadequate technological support. Therefore, adaptive and innovative managerial strategies are required, including strengthening regulations, enhancing human resource capabilities, and developing digital archival systems based on information technology. Digital transformation in educational archiving is expected to improve efficiency, security, and accessibility of educational data sustainably. Keywords: educational archiving, archive management, digital transformation, information systems, educational governance